The identification of antioxidant and ACE-I peptides in different turkish ripened cheeses - Turan, Neslihan; Durak, Muhammed Zeki (SPRINGER INDIA, 2022)
The principal purpose of this study was to determine antioxidant and ACE-inhibitory (angiotensin converting enzyme) activities of 5 ripened Turkish cheese varieties (Kashar, Erzincan Tulum, Izmir Tulum Gruyere, Mihalic). Among the water-soluble extracts with a molecular weight smaller than 3 kDa Gruyere and Erzincan Tulum exhibited the highest free radical scavenger activity in FRAP (Ferric Reducing Ability of Plasma) and ABTS [2,20-azino-bis-(3-ethylbenzothiazoline-6-sulphonic acid)] assays, respectively. For the inhibition of ACE, Mihalic was more effective than others. The water-soluble extracts of five cheese were analyzed with liquid chromatography-tandem mass spectrometry to identify the peptide sequences. Totally 394 peptides were sequenced; of these, 134 from alpha s1-casein, 44 from alpha s2-casein, 198 from beta-casein, and 18 from kappa-casein. Among these sequences, 48 peptides were reported as bioactive with the activities including ACE-inhibitory, antioxidant, antimicrobial, DPP-IV inhibitory, antidiabetic, immunomodulating, antithrombotic, anti-inflammatory, and inhibition of cholesterol solubility. These results showed that Turkish cheeses are good sources of bioactive peptides.
Keywords: Bioactivity; Orbitrap; ABTS; FRAP; WATER-SOLUBLE EXTRACTS; BIOACTIVE PEPTIDES; FUNCTIONAL PEPTIDES; PARMIGIANO-REGGIANO; INHIBITORY ACTIVITY; MILK CHEESE; VITRO; PROFILE; COW; Food Science & Technology